IMPLEMENTASI KURIKULUM BARU TAHUN 2013 MATA PELAJARAN PENDIDIKAN JASMANI (STUDI DESKRIPTIF KUALITATIF PADA SDN CILENGKRANG) - Suherman, Ayi (Universitas Pendidikan Indonesia, 2014)
This study focused on the implementation of the curriculum in 2013 with respect to all aspects of planning, implementation, and evaluation activities in the physical education subject Elementary School Cilengkrang Sumedang. The study was intended to obtain an overview of the problem of how teachers develop curriculum 2013. The method used is descriptive method with qualitative naturalistic approach by describing, analyzing and discussing the data sourced directly from the principal, teachers and students during the learning process that comes with the syllabus documents and lesson plan and document the results. The results showed that the implementation of the curriculum in 2013 has not been in accordance with the demands of school teachers even seem difficult, therefore, to improve the quality of the learning process is recommended for teachers to understand more about the implementation of the curriculum in 2013 and the principals and related parties in order to complete the infrastructure for learning improving the quality of processes and maximum learning results.Keywords: implementation, curriculum 2013, physical education, elementary school.